Lymphatic system and neoplastic diffusion: experimental aspects - Perdomo, Roberto; Gardiol, Valdo C (Cirugía del Uruguay, 2021)
An experiment was conducted with W alker 256 carcinoma transplanted to rat testicles and this showed that when the lymph route is blocked or altered the regional diffusion of the tumor seems to be favoured. lf lymph interruption lasts for more than 48 hours after implantation of the tumor, the nodes become affected. Lymphatic system value in the cause of resistence to diffusion is discussed in relation to other details of the experiment. An inverse relationship seems to exist between the number of node metastasis and the overall number of other metastasis.